Breaking the odds: A rare case of bilateral breast angiosarcoma - Pizzileo , Sara Maria; Pizzolorusso, Francesco; Errico, Angelo; Iacobellis, Giulia; Lamacchia, Annalisa; De Lorenzis, Stefano; Bambace, Santa; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2025)
Breast angiosarcoma is an extremely rare and aggressive tumor, presenting several challenges in diagnosis and treatment. Imaging techniques play a crucial role in the early diagnostic assessment, initially allowing for a differential diagnosis with other breast tumors (using ultrasound and MRI techniques) and subsequently for patient follow-up through CT and MRI examinations.Currently, there is no standardized or unified treatment protocol, especially regarding metastatic forms, where the use of chemotherapy or radiotherapy remains subject of debate.The rarity of this tumor entity suggests the need for future research and multidisciplinary collaboration in order to further optimize diagnostic accuracy and treatment options.